Comparison of Judge's Decisions Regarding the Crime of Murder - Guterres, Deny Susilo; Deddy R. CH. Manafe; Rosalind Angel Fanggi (PT FORMOSA CENDEKIA GLOBAL, 2024)
The judge's considerations are one of the most important aspects in determining the realization of the value of a judge's decision which contains justice and legal certainty, besides that it also contains benefits for the parties concerned so that the judge's considerations must be addressed carefully, well and carefully. The formulation of the problem in this research is, How does the Judge's Decision Compare with the Crime of Murder? This research uses normative juridical legal research methods. The data collection technique is based on the type of approach in this paper, namely the statutory approach and the conceptual approach. Analyzed using descriptive methods. The results of the research show that the comparison of the judge's decision regarding the crime of murder from the three decisions can be seen from two aspects, juridical and non-juridical. Apart from that, the judge has the authority to update the law and find the law, so that the judge is able to see the weight of the crime and the suitability of the evidence. decide decisions that make each decision different, with the same type of crime, but a different panel of judges. This is what makes this research interesting compared to others